2018
DOI: 10.1111/pce.13479
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylation of (Z)‐3‐hexenol informs intraspecies interactions in plants: A case study in Camellia sinensis

Abstract: Plants emit a variety of volatiles in response to herbivore attack, and (Z)‐3‐hexenol and its glycosides have been shown to function as defence compounds. Although the ability to incorporate and convert (Z)‐3‐hexenol to glycosides is widely conserved in plants, the enzymes responsible for the glycosylation of (Z)‐3‐hexenol remained unknown until today. In this study, uridine‐diphosphate‐dependent glycosyltransferase (UGT) candidate genes were selected by correlation analysis and their response to airborne (Z)‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
123
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(126 citation statements)
references
References 62 publications
(115 reference statements)
3
123
0
Order By: Relevance
“…The apparent Michaelis constant (Km) value of UGT91Q2 for nerolidol was 19.71 ± 2.76 µM (Fig. f) measured at optimized conditions (Figs S4–S7), which was two‐fold lower than the apparent Km value of CsUGT85A53 and UGT85K11 for ( Z )‐3‐hexenol (27.77 and 40.66 μM, respectively), two previously identified enzymes in tea plants involved in the glucosylation of ( Z )‐3‐hexenol (Ohgami et al , ; Jing et al , ). The result suggested that UGT91Q2 shows a high affinity to nerolidol.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…The apparent Michaelis constant (Km) value of UGT91Q2 for nerolidol was 19.71 ± 2.76 µM (Fig. f) measured at optimized conditions (Figs S4–S7), which was two‐fold lower than the apparent Km value of CsUGT85A53 and UGT85K11 for ( Z )‐3‐hexenol (27.77 and 40.66 μM, respectively), two previously identified enzymes in tea plants involved in the glucosylation of ( Z )‐3‐hexenol (Ohgami et al , ; Jing et al , ). The result suggested that UGT91Q2 shows a high affinity to nerolidol.…”
Section: Resultsmentioning
confidence: 91%
“…In Arabidopsis , the UGTs that displayed catalytic activity in vitro towards terpenoids were restricted to groups D, E, G, H and L of the phylogenetic tree of the GT1 multigene family (Caputi et al , ; Cui et al , ). In the tea plant, some UGTs belonging to the subgroups A (UGT94P1) and G (UGT85K11 and UGT85A53) showed broad substrate specificity towards monoterpenes (Jing et al , ; Ohgami et al , ). Thus, UGTs involved in the glucosylation of nerolidol are most likely members of the UGT subgroups A, D, E, G, H and L, which comprise 218 UGTs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations